Collaborative Governance in Implementing Child-Friendly City Policy: Bandung City Case Study - Yolanda Rossi; Ely Sufianti; Abdul Rahman; Nita Nurliawati (Goodwood Publishing, 2026)
Purpose: This study examines the collaborative governance model in the implementation of the Child-Friendly City (Kota Layak Anak/KLA) policy in Bandung City, identifies the key driving and inhibiting factors, and formulates strategic efforts to strengthen multi-stakeholder collaboration in child protection policy. Methodology: A qualitative case study approach was employed, using in-depth interviews, observations, and document analysis. Data were analyzed using an interactive qualitative model guided by the Ansell and Gash collaborative governance framework, focusing on initial conditions, institutional design, facilitative leadership, and collaborative processes. Results: The findings show that collaborative governance in the implementation of KLA in Bandung is present but not yet optimal. Collaboration remains fragmented across sectors, with challenges including unequal stakeholder capacity, limited incentives for non-governmental actors, and insufficient meaningful child participation. Existing initiatives rely heavily on administrative coordination, rather than sustained trust-based collaboration. Conclusions: The KLA policy’s success is strongly influenced by the quality of collaborative governance. Strengthening collaboration requires improving initial collaborative conditions, institutionalizing cross-sector mechanisms, enhancing facilitative leadership, and promoting inclusive stakeholder engagement, particularly at the community level. Limitations: This single-case study may limit the generalizability of the findings to other regions. Contributions: This study enriches the collaborative governance literature by applying the Ansell and Gash model to child protection policy. It also provides practical recommendations for strengthening multi-stakeholder collaboration for more effective Child-Friendly City initiatives.